My autistic awakening : unlocking the potential for a life well lived - Harris, Rachael Lee, 1969- (Rowman and Littlefield, 2015)
Rachael Lee Harris spent her early childhood locked in an autistic fog until beginning her journey from a fragmented world to one in which things began to make sense. Rachael's determination to take her place in society led her down many paths, from beauty therapist to Catholic nun, from mother and wife to divorcee and working mom. Today, she is a psychotherapist specializing in helping others on the Autism Spectrum. Rachael's story explores areas such as schooling, family relationships, employment, travel, and faith culminating in monastic life, motherhood, dating, and marriage. Through her story, we get a more "rounded" positive vision of how an autistic life can develop and insight into the benefits of being "on the spectrum" alongside the very real picture of its challenges. Addressing the culture of disability and negativity that surrounds so much of the public perception of the Autism Spectrum, Rachael presents a more moderate and perhaps more objective assessment of her own life experiences, as well as the potential for others on the Spectrum.--Publisher description